Defense Expenditures Current Account Deficit and Economic Growth Relationship: The Case of NATO Countries* - TORUSDAĞ, Asst. Prof. Dr. Mustafa; GÜL, Professor Dr. Ekrem (The journal of contemporary issues in business and government, 2021)
In the economic literature, there are not many studies in the empirical literature on defense spending, current account deficit and its effect on economic growth. In this study, to investigate the relationship between NATO countries for the 1990-2017 period. In the analyzes, Emirmahmutoğlu and Köse (2011) and Dumitreschu-Hurlin (2012) panel causality tests were used. As a result of the analysis, one unit increase in defense expenditures increased economic growth by 0.878 units, according to the first model in which GNP variable is taken as dependent variable for NATO countries. Therefore, it has been determined that there is a positive externality relationship between defense expenditures and economic growth. According to the second model, in which defense expenditures are taken as dependent variable, a positive relationship was determined between military expenditures and arms exports and imports. According to Dumitreschu-Hurlin (2012) panel causality test, one-way causality relationship was found from current account deficit to economic growth and current account deficit to military spending. Supporting this result, Emirmahmutoğlu and Köse (2011) found a one-way causality relationship from economic growth to military spending, from current account deficit to economic growth and from military spending to current account deficit, according to the panel causality analysis.